Six magical tales step 1 and 2 books, a collection of six early readers (New York Random House, 2018)
Six stories featuring twin genies, Shimmer and Shine, see them race magic carpets, have a movie night, celebrate a birthday, and enjoy a winter day
Magical mermaids! -- Happy birthday to you! -- Meet Shimmer and Shine! -- Movie night magic! -- Magic carpet race! -- Winter wishes!
"Step 1 and 2 books. A collection of six early readers."
At head of title: Nickelodeon Shimmer and Shine
2